SEJAUH MANAKAH PENELITIAN UKURAN PERUSAHAAN? SEBUAH ANALISIS BIBLIOMETRIK DENGAN VOSVIEWER DAN STUDI LITERATUR - Fakhrul Fakhrudin; Sri Andriani; Ahmad Fahrudin Alamsyah (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research analyzes the impact of company size on business performance, focusing on profitability, leverage, financial performance, and institutional ownership, through a bibliometric approach and literature review. Data was collected from 500 scientific publications sourced from Google Scholar and Emerald, covering the period from 2020 to 2025, and analyzed using VOSviewer to map research trends. The findings show that company size significantly affects profitability and financial performance, with larger companies tending to be more profitable due to economies of scale and better resource access. However, high leverage can weaken these benefits, especially for smaller companies that are more vulnerable to financial risks. Institutional ownership, which is more dominant in larger companies, supports better governance and reduces the negative impact of leverage. This study confirms that company size is an important variable in financial strategy and governance, with significant implications for risk management and business decision-making.